Sinigrin Enhanced Antiasthmatic Effects of Beta Adrenergic Receptors Agonists by Regulating cAMP-Mediated Pathways - Chu, Simeng; Liu, Wenjuan; Lu, Yujie; Yan, Menglin; Guo, Yingying; Chang, Nianwei; Jiang, Min; Bai, Gang (Frontiers in Pharmacology, 2020)
Millions of patients suffer from asthma worldwide. However, the first-line drugs used to treat asthma, namely the beta-adrenergic receptor agonists (β-agonists), are not recommended for use as monotherapy because of their severe dose-related side effects. This limitation has prompted the search for new therapies, which can be used in conjunction with BAs so that lower doses can be administered. Sinigrin is a major compound found in many anti-asthmatic medicinal plants. In this study, we explored the anti-asthmatic activity of sinigrin when used in combination with β-agonists and its underlying mechanism. Sinigrin enhanced the asthma-relieving effects of isoproterenol and reduced the effective isoproterenol dose in an acute-asthma model in guinea pigs. Mechanistically, sinigrin enhanced the cAMP levels induced by β-agonists by inhibiting PDE4. The resulting increase in cAMP levels stimulated the activity of the downstream effector protein kinase A, which would be expected to ultimately induce the relaxation of airway smooth muscle. In conclusion, sinigrin enhances the asthma-relieving effects of β-agonists by regulating the cAMP signaling pathway and represents a potential add-on drug to β-agonists for the treatment of asthma.